A population study of adult onset limb-girdle muscular dystrophy. Issue 4 (August 1985) - Yates, J R; Emery, A E
Abstract : Complete ascertainment of adult onset limb-girdle muscular dystrophy in the Lothian Region of Scotland was attempted. Ten index cases were identified giving a prevalence of 1.3 per 100 000 (0.9 per 100 000 for cases where the diagnosis of muscular dystrophy was supported by both electromyographic and muscle biopsy findings). In these 10 sibships there had been 11 affected subjects, significantly less than the 16.5 cases expected for autosomal recessive inheritance. Excluding cases suspected of being Becker muscular dystrophy, the prevalence was 0.7 per 100 000 (0.3 per 100 000 for proven cases of muscular dystrophy) and there remained a significant difference between the number of cases observed (5) and the number expected (9.1) for autosomal recessive inheritance. The prevalence of limb-girdle muscular dystrophy with onset in adult life has apparently declined over the past 30 years, as would be expected with the recognition of other conditions which cause the same pattern of weakness, making this a relatively rare disorder which should only be considered when other diagnoses have been excluded. The possibility that some cases diagnosed as limb-girdle muscular dystrophy may have had Becker muscular dystrophy emphasises the urgent need for a greater understanding of the biochemical basis of these conditions so that such diagnostic and genetic counselling dilemmas can be resolved.